Analisis Sistem Aplikasi Supply Chain Management Telkom (SCMT) Untuk Teknisi di PT. Telkom Kandatel Langsa - Tesa Asmita Asmita; Rizalul Akram (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2021)
Application systems are a sub class of software that take advantage of the ability of a computer directly to perform a task that the user wants. PT. Telkom Indonesia (Persero) Tbk (Telkom) is a State-Owned Enterprise (BUMN) engaged in information and communication technology (ICT) services and telecommunications networks in Indonesia. PT Telkom also provides the procurement of materials and services for the installation of internet network devices. Development of an application system for checking the activation of the installation of material goods to customers and can assist the admin in checking the activation of the installation of material goods to customers. The development of the SCMT application has succeeded in checking the activation of the installation of material goods to customers. That way the admin can see the activation of the installation of material goods to customers. The development of the SCMT application is made using DFD to help understand the application system, and the development of this application uses ERD to determine relationships between tables.